2009
DOI: 10.1007/s00436-009-1350-z
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of and risk factors for Toxoplasma gondii antibodies among asymptomatic blood donors in Egypt

Abstract: A cross-sectional study was conducted to evaluate the seroprevalence of and risk factors for Toxoplasma gondii antibodies in 260 blood donors seen at blood banks in Mansoura University Hospital, Egypt. Blood donors were interviewed about sociodemographic characteristics and risk factors for T. gondii infection. A blood sample was taken to document their T. gondii antibody status using enzyme-linked immunosorbent assay. Overall, 155 (59.6%) of 260 blood donors were positive for anti-T. gondii IgG antibodies. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
7
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 17 publications
13
57
7
2
Order By: Relevance
“…Similar results from Mali showed that the risk of infection increases with the increase in maternal age (Ouologuem et al 2013). This is supported by studies from Arabs countries (Mohammad et al 2012;Al-Qurashi et al 2001) and a large study from Egypt which showed that the prevalence of Toxoplasma infection increases with age (Elsheikha et al 2009). On the other hand, age is not found to be associated with toxoplasma infection among Chinese pregnant women (Sun et al 2006).…”
Section: Maternal Agementioning
confidence: 70%
See 2 more Smart Citations
“…Similar results from Mali showed that the risk of infection increases with the increase in maternal age (Ouologuem et al 2013). This is supported by studies from Arabs countries (Mohammad et al 2012;Al-Qurashi et al 2001) and a large study from Egypt which showed that the prevalence of Toxoplasma infection increases with age (Elsheikha et al 2009). On the other hand, age is not found to be associated with toxoplasma infection among Chinese pregnant women (Sun et al 2006).…”
Section: Maternal Agementioning
confidence: 70%
“…Kitchen hygiene should be improved, including avoiding drinking contaminated liquids or consuming inadequately washed vegetables and fruits. Health education about preventive measures is the most accessible and cost-effective method (Elsheikha et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot grantee that it was responsible for pregnancy loss in this study. In pregnancy, it is mandatory to perform additional conclusive tests that must include, IgG avidity test, PCR, IgA and IgE, on individuals with both positive IgG and IgM [19], because Toxoplasma-specific IgM antibodies may be persist as long as 18 months after acute acquired infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…Samples from 385 healthy blood donors from central Turkey were examined for anti-T. gondii antibodies using the indirect fluorescent antibody test (IFAT) and enzyme-linked immunosorbent assay (ELISA). The seroprevalence of the anti-T. gondii IgG and IgM antibodies was 19.5% and 2.33% with IFAT, respectively, and 20.25% and 2.33% with ELISA, respectively (7)(8)(9). Different studies conducted in Iran have also produced different results.…”
Section: Introductionmentioning
confidence: 99%